La radiación de frenado en campos magnéticos fuertes (ING) - Semionova N., L. (1989)
We present an analysis of the Bremsstrahlung transition functions depending on the total spin polarization of the electron along the external magnetic field and the linear or circular polarization of the emitted radiation. Also we determine the ground-state-dominance for the electron to jump to the ground Landau level, if the magnetic field strength is of the order Bcrit = m2c3 / eh  = 4,414*1013 Gauss. As a numerical application of our theoretical calculus on this process, we study the lines of 58, 110 and 155 Kev of the spectrum of the pulsar Her X-1. It permits us to assure that those spectral lines correspond to the fundamental, second and third harmonics, for this process.Subject headings: x-rays-magnetic fields- Landau levels